PENGEMBANGAN PERANGKAT PEMBELAJARAN OPERASIONAL AMPLIFIER LM 741 BERBASIS INKUIRI UNTUK MELATIHKAN KETERAMPILAN BERPIKIR SISWA KELAS XI TEKNIK AUDIO VIDEO SMKN 2 PENAJAM PASER UTARA - Rohmat, Rohmat; Rijanto, Tri; Suprianto, Bambang (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
Abstract 2013 curiculum has general learning aim which consist of affective, cognitive, and skills aspect. Thinking skill is part of the main competence which much be learnt in 2013 curiculum. This research develops the learning material in the inquiry based operational amplifier LM 741 discussion to train students? thinking skills. This research aims to measure the validity, effectiveness and practicality of the of the developed learning material. The steps of instructional development of learning material using 4D model by Thiagarajan. Four steps which have been conducted are introduction, design, validation, empiric test and revision The data collecting technique used are observation, interviews, validation, test and non-test. The descriptive analysis is used to analyzed data. The research is conducted at eleventh grade Audio Video Engineering Program at SMKN 2 Penajam Paser Utara. There are 26 students become the research population. The result of the first research shows the validity of learning material get the average of 3.33 among the scale 0-4 and the reliability coefficient of 0.85. The second research result shows that effectivity of the learning set consist of spiritual affective competence achievement which is 3.42; social affective competence is 3.34; cognitive competence is 3.34; thinking skill competence is 3.39 and get criteria of very good, the working skills competence is 3.49; and students? response who like the learning set is 90,38%. The practicallity of the learning material gets the score for 3.86 from the learning implementation. The data analysis shows that (1) learning material get a very good validity, (2) the learning material is very effective in the use based on the competence achievement and students? positive response, and (3) the learning material is very practical based on the observation of the learning implementation. Keywords: Learning Material, Inquiry, Thinking Skills, Operational Amplifier, Validity, Effectivity, and Practicallity.